Spectra of low-energy secondary electrons in the interaction of relativistic electrons with aluminum foil - Vit’ko, V.; Kovalenko, G.; Karpus, S.; Semisalov, I.; Shopen, O. (Problems of Atomic Science and Technology, 2022)
The integral yields of secondary low-energy electrons (with energies up to 50 eV) in the interaction of primary electrons 10…30 MeV with 50 μm aluminum foil have been studied. It is shown that the proposed method for approximating the spectra of low-energy electron emission in the measured part of the spectrum (E < 4.2 eV) makes it possible to obtain data on the absolute values of the spectra of electrons emitted from the target. It has been established that the spectra of secondary low-energy electrons, depending on the energy of primary electrons, have a maximum in the range of 1.3…1.6 eV, and the FWHM values are in the range of 2.7…3.8 eV.